2019
DOI: 10.3390/rs11050508
|View full text |Cite
|
Sign up to set email alerts
|

A Modeling Framework for Deriving Daily Time Series of Evapotranspiration Maps Using a Surface Energy Balance Model

Abstract: Surface energy balance models have been one of the most widely used approaches to estimate spatially distributed evapotranspiration (ET) at varying landscape scales. However, more research is required to develop and test an operational framework that can address all challenges related to processing and gap filling of non-continuous satellite data to generate time series of ET at regional scale. In this study, an automated modeling framework was developed to construct daily time series of ET maps using MODIS im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 106 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…The sensibility of satellite-based solutions have to cloud levels [ 55 , 123 , 124 ], and the questionable results of the use of air humidity, wind speed, and precipitation retrieved from the NASA/POWER gridded weather dataset [ 56 ] suggest some disadvantages of satellite-based solutions. However, gridded weather databases provide applicable temperature and radiation parameters [ 56 ], making room for future research of models that combine IoT sensing technologies shown in Table 1 and the proposed model of irrigation planning.…”
Section: Discussionmentioning
confidence: 99%
“…The sensibility of satellite-based solutions have to cloud levels [ 55 , 123 , 124 ], and the questionable results of the use of air humidity, wind speed, and precipitation retrieved from the NASA/POWER gridded weather dataset [ 56 ] suggest some disadvantages of satellite-based solutions. However, gridded weather databases provide applicable temperature and radiation parameters [ 56 ], making room for future research of models that combine IoT sensing technologies shown in Table 1 and the proposed model of irrigation planning.…”
Section: Discussionmentioning
confidence: 99%
“…Khand et al [35] developed an automated modeling framework to construct daily time series of ET maps, addressing the challenges related to processing and gap filling of non-continuous satellite data using the moderate resolution imaging spectroradiometer (MODIS) imagery and the Surface Energy Balance System (SEBS) model. The daily ET maps generated by this modeling framework captured the spatial and temporal variations (2001-2014) of ET across Oklahoma, USA.…”
Section: Inter-comparison and Performance Evaluation Of Several Et Momentioning
confidence: 99%
“…This paper reviews the single-source energy balance model, which differs somewhat from the two-source models for determining ET (Figure 2). Khand et al (2019) used a surface energy balance model for estimating spatially distributed ET, especially on varying landscape scales. This uncertainty-limiting approach for reviewing South African ET was proposed in this study in order to enhance the high resolution level encountered during the continuous observation process (Gibson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%